CONSUMPTION OF BEEF BALI CATTLE AND IT’S EFFECTS ON RATS PLASMA LIPOPROTEIN PROFILE - Suarsana, I Nyoman (Buletin Veteriner Udayana, 2016)
Consumption of beef in Indonesia is continuously increasing. Aside from being a source of protein, beef also contains all essential amino acids, vitamins, fats and cholesterol making it an ideal choice for consumers. This study aims to analyze the consumption of beef bali on rats plasma lipoprotein levels. A total of 15 male rats Spraque Dawlly average body weight of 90-100g was used in this study. They were sub-divided into five  groups: a control group, without treatment (I), fed- beef group was treated from 7 th day (II),  fed-beef group was treated from 5 th day (III),  fed-beef group was treated from 3 th day (IV), and fed-beef group was treated from 1 st day (V).  At the end of the experiment, i.e 9 th days all groups of rats were euthanasia with cethamine-HCl. Blood was taken through the heart and placed in tubes containing EDTA to obtain plasma. Levels of  cholesterol, triglycerides,  HDL was analyzed by spectrophotometric method using cholesterol KIT (Ref10028), TGA (Ref10720P), and HDL (Ref10018). LDL levels were calculated using the formula: LDL= total cholesterol-(TG/5)-HDL. The results showed that  rats  given beef bali cattle for 8 days was lead to increased plasma triglyceride levels significantly (P<0.05), while cholesterol, HDL (high density lipoprotein) and LDL (low density lipoprotein) plasma levels is not increased.
Keywords: beef; bali catlle; lipoprotein; plasma